A method to quantify regional axonal transport blockade at the optic nerve head after short term intraocular pressure elevation in mice. (July 2020) - Korneva, Arina; Schaub, Julie; Jefferys, Joan; Kimball, Elizabeth; Pease, Mary Ellen; Nawathe, Manasi; Johnson, Thomas V.; Pitha, Ian; Quigley, Harry
Abstract: Axonal transport blockade is an initial step in retinal ganglion cell (RGC) degeneration in glaucoma and targeting maintenance of normal axonal transport could confer neuroprotection. We present an objective, quantitative method for assessing axonal transport blockade in mouse glaucoma models. Intraocular pressure (IOP) was elevated unilaterally in CD1 mice for 3 days using intracameral microbead injection. Longitudinal sections of optic nerve head (ONH) were immunofluorescently labeled for myelin basic protein (MBP) and amyloid precursor protein (APP), which is transported predominantly orthograde by neurons. The beginning of the myelin transition zone, visualized with the MBP label, was more posterior with elevated IOP, 288.8 ± 40.9 μm, compared to normotensive control eyes, 228.7 ± 32.7 μm (p = 0.030, N = 6 pairs). Glaucomatous regional APP accumulations in retina, prelaminar ONH, unmyelinated ONH, and myelinated optic nerve were identified by objective qualification of pixels with fluorescent intensity greater than the 97.5th percentile value of control eyes (suprathreshold pixels). This method segregated images with APP blockade from those with normal transport of APP. The fraction of suprathreshold pixels was significantly higher following IOP elevation than in normotensive controls in the unmyelinated ONH and myelinated nerve regions (paired analyses, p = 0.02 and 0.003, respectively, N = 12), but not in retina or prelaminar ONH (p = 0.91 and 0.08, respectively). The mean intensity of suprathreshold pixels was also significantly greater in glaucoma than in normotensive controls in prelaminar ONH, unmyelinated ONH and myelinated optic nerve (p = 0.01, 0.01, 0.002, respectively). Using this method, subconjunctival glyceraldehyde, which is known to worsen long-term RGC loss with IOP elevation, also produced greater APP blockade, but not statistically significant compared to glaucoma alone. Systemic losartan, which aids RGC axonal survival in glaucoma, reduced APP blockade, but not statistically significant compared to glaucoma alone. The method provides a short-term assessment of axonal injury for use in initial tests of neuroprotective therapies that may beneficially affect RGC transport in animal models of glaucoma. Highlights: A method to quantify axonal transport blockade in mouse optic nerve is presented. Localized accumulation in four zones of the optic nerve was quantified. The method was applied to glaucoma pretreated with glyceraldehyde or losartan. Method can assess neuroprotection in glaucoma models at an early time point.